Locational patterns of warehousing facilities in the City of Cape Town municipality - Masilonyane Mokhele; Brian Fisher-Holloway (Town and Regional Planning, 2023)
The proliferation of globalisation and e-commerce has led to an increasing number of warehousing facilities in cities and regions, which may contribute to the negative externalities of air pollution, noise pollution, and traffic congestion. Despite the close relationship between logistics and different sectors of the economy, there is a paucity of literature on the connection between warehousing and different land-use categories. Focusing on the City of Cape Town municipality in South Africa, the article aims to analyse the locational patterns of warehousing facilities relative to the transport infrastructure and the industrial, retail, and office land use. The study was based on a descriptive quantitative design wherein kernel density was employed in ArcGIS to analyse the locational patterns of warehousing facilities across the municipality. Data on the floor area of the industrial, retail, and office land use were classified into several ranges to ascertain the intensity of the land use relative to the concentration of the warehousing facilities. It was discovered that warehousing facilities cluster in the highly accessible areas within the municipality, namely the port’s environs, in the vicinity of the main junctions, and adjacent to arterial roads, which provide connections to the national roads. The areas with the highest concentration of warehousing facilities also accommodated the most significant percentage of industrial and retail land use. It is recommended that the existing warehousing clusters be prioritised in future warehousing development or consolidation, and that the future increase of the industrial and retail land use within the City of Cape Town municipality include a commensurate increase of space for warehousing facilities or vice versa.